Effects of Artemisia ordosica polysaccharide on growth performance and antioxidant capacity in broilers - Haidong Du; Yuanyuan Xing; Xiao Jin; Sumei Yan; Binlin Shi (Journal of Applied Animal Research, 2023)
This study aimed to investigate the effects of dietary Artemisia ordosica polysaccharide (AOP) supplementation on broilers’ growth performance and antioxidant function. A total of 288 1-day-old Arbor Acre broilers were randomly divided into 6 groups with 6 replicates each (n = 8). The groups contained a control diet group (basal diet, CON), an antibiotic diet group (basal diet + 50 mg/kg chlortetracycline, CTC) and AOP diet groups (basal diet containing 250, 500, 750, 1000 mg/kg AOP, respectively). The experiment included starter phase (days 1–21) and grower phase (days 22–42). The results showed that adding 750 mg/kg AOP increased the average daily gain (ADG), decreased feed/gain (F/G). Adding 500–1000 mg/kg AOP in the diet of broilers increased the activities of total antioxidant capacity (T-AOC), catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) in spleen, liver and small intestine (P < 0.05). The addition of AOP increased the gene expression levels of nuclear factor E2-related factor 2 (Nrf2), heme oxygenase-1 (HO-1), CAT, GSH-Px and SOD in Nrf2 signalling pathway. Our data suggested that AOP could improve broilers’ growth performance and antioxidant function. Therefore, AOP may be used as a growth promotion and antioxidant feed additive in broiler chickens instead of antibiotics.